The Role of Contract Law in Improving Legal Certainty for Business Actors - Tri Arta Udayana, Anak Agung Bagus; Pramana Putra, Made Aditya (Journal of Law, Politic and Humanities, 2025)
Legal certainty is a crucial pillar in creating a conducive business climate, especially through contract law regulated by the Civil Code ( KUHPerdata ). This research employs a normative approach with an analysis of legislation and literature review to evaluate the role of contract law in enhancing legal certainty for business actors in Indonesia. Through descriptive qualitative analysis, it is found that the essential aspects supporting legal certainty include the requirements for valid contracts, implementation regulations, dispute resolution mechanisms, and the recognition of electronic contracts. However, challenges such as a lack of legal understanding among business actors, regulatory uncertainty, and an inefficient dispute resolution system still hinder the effective implementation of contract law. This study emphasizes the importance of education and training on contract law for business actors, particularly SMEs, as a strategic step to improve legal certainty.